The heritagisation of the Pokfulam Fire Dragon Dance in Hong Kong - Stephanie Po Yin Chung; Lachlan Barber (Built Heritage)
Abstract In this paper, we examine the heritagisation of a local spiritual ritual in Hong Kong as an example of expanding the field of built heritage studies to encompass relevant nonmaterial heritage. Herein, we present the case that a listed example of intangible cultural heritage in Hong Kong, namely, the Pokfulam Fire Dragon Dance, is an integral part of one of the few remaining villages in urban Hong Kong. Specifically, we argue that Pokfulam village has been protected from demolition in part as a result of the work that has gone into recognising and promoting the heritage significance of the dance. Through an in-depth study using a mixture of historical and qualitative methods, including participant observation and key informant interviews, the paper presents an unusual example of the blurring of tangible and intangible heritage. Building on recent work in heritage studies that challenges established dichotomies, we show how these categories, which have separate mechanisms and policy frameworks, are, in this case, mutually constituted. The paper also demonstrates how heritagisation is a dynamic and, at times, pragmatic reinterpretation of cultural meaning involving multiple intersecting conditions, resources and actions. These include the changing political context, opportunities for heritage recognition, and organisational and programming changes to expand the appeal of the event. This case study contributes to the interest in the dynamics of heritagisation processes, with a focus on contextualising the agency of local actors, with a variety of different outcomes.